Reinforcing Halal Supply Chain Legitimacy: A Juridical Analysis of MUI Fatwa on Porcine Blood Based Animal Feed - Abdul Rachman; Muhammad Ikhlas Rosele; Muhammad Safwan Harun; Akbar Sarif; Imamuddin Imamuddin (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the position of MUI Fatwa Number 08/Ijtima' Ulama/VIII/2024 in determining the halal status of livestock that consume feed containing pig's blood and its implications for strengthening the halal food supply chain in Indonesia. This issue is important because the use of pig blood meal in the feed industry creates legal uncertainty and has the potential to reduce consumer confidence in halal products. The research uses a descriptive qualitative method with a normative juridical approach, based on secondary data in the form of related fatwas and halal product assurance regulations. The results of the study show that the fatwa provides strict normative provisions regarding the halalness of animal products, especially through the affirmation that animal feed must meet halal standards. This fatwa also strengthens the aspects of accountability and transparency in the halal certification system, especially in the upstream sector of the supply chain. In addition, the implementation of fatwas contributes to increasing the effectiveness of supervision and public trust in the integrity of halal products. The implications of this study show that fatwas have a strategic role in supporting the strengthening of regulations by BPJPH, especially related to the obligation of halal certification on animal feed. For LPH, these findings provide operational guidelines in improving the accuracy of product audits and testing. Overall, the integration of fatwas into the halal supply chain system has been proven to strengthen the legitimacy, consistency, and sustainability of the halal industry in Indonesia.